Vanishing voices : the extinction of the world's languages - Nettle, Daniel (OUP E-Books., 2000)
Suggests links between disappearing linguistic diversity and environmental issues. The authors argue that it is part of the larger picture of the world's collapsing ecosystem, and that the causes of language death, like those of ecological destruction, lie at the crossroad of ecology and politics.